1992
DOI: 10.1002/1098-108x(199203)11:2<163::aid-eat2260110207>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Primary anorexia nervosa: Gastric emptying and antral motor activity in 53 patients

Abstract: In 53 consecutive patients with primary anorexia nervosa, gastric emptying of a semisolid meal was significantly slower than in 24 healthy subjects. Slow emptying tended to be associated with low serum potassium, low body weight, and long illness duration. Antral contraction amplitudes were lower than in healthy subjects and failed to increase postcibally, whereas contraction frequency and rhythmicity seemed unaffected. After the gastric prokinetic agent, cisapride, 8 mg intravenously administered double‐blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…'6 In experimental animals the prodromal (preejection) phase of the emetic reflex is characterised, among the other vagally mediated autonomic outputs, by suppression of the gastric antral pacemaker and the induction of electrical dysrhythmias.17 Electrical dysrhythmias are associated with loss of electromechanical coupling in the antrum, resulting in impaired antral contractility and delayed gastric emptying. '8 19 The correlation between these electromechanical abnormalities and symptoms of early satiety, postprandial discomfort, bloating, nausea, and vomiting has been clearly established in a number of clinical disorders.20-26 Such symptoms are commonly reported in adults with anorexia nervosa.2 Studies of foregut motor function and gastric emptying in adults with anorexia and bulimia nervosa have consistently shown that the amplitude of gastric antral contractions is impaired during fasting and after feeding, and that gastric emptying is often significantly delayed in patients with anorexia nervosa.34 [27][28][29] Therefore it has been suggested that these foregut motility disorders may contribute to or perpetuate the eating disorder by inducing nausea and other aversive food related sensations, by causing bloating and thereby exacerbating the patient's fear of fatness and distorted body image.4 The correlation between gastrointestinal symptoms and disordered gastric emptying was not always clear, however.30 31 Although there is general agreement about the frequency of gastrointestinal dysmotility in adult anorexia nervosa, much less is known about the causes of the dysmotility and uncertainty still exists as to whether this is a primary, and therefore pathogenetically relevant, or secondary phenomenon. It seems likely from the present and previous studies that it is a secondary phenomenon, possibly related to the degree of malnutrition.…”
Section: Resultsmentioning
confidence: 99%
“…'6 In experimental animals the prodromal (preejection) phase of the emetic reflex is characterised, among the other vagally mediated autonomic outputs, by suppression of the gastric antral pacemaker and the induction of electrical dysrhythmias.17 Electrical dysrhythmias are associated with loss of electromechanical coupling in the antrum, resulting in impaired antral contractility and delayed gastric emptying. '8 19 The correlation between these electromechanical abnormalities and symptoms of early satiety, postprandial discomfort, bloating, nausea, and vomiting has been clearly established in a number of clinical disorders.20-26 Such symptoms are commonly reported in adults with anorexia nervosa.2 Studies of foregut motor function and gastric emptying in adults with anorexia and bulimia nervosa have consistently shown that the amplitude of gastric antral contractions is impaired during fasting and after feeding, and that gastric emptying is often significantly delayed in patients with anorexia nervosa.34 [27][28][29] Therefore it has been suggested that these foregut motility disorders may contribute to or perpetuate the eating disorder by inducing nausea and other aversive food related sensations, by causing bloating and thereby exacerbating the patient's fear of fatness and distorted body image.4 The correlation between gastrointestinal symptoms and disordered gastric emptying was not always clear, however.30 31 Although there is general agreement about the frequency of gastrointestinal dysmotility in adult anorexia nervosa, much less is known about the causes of the dysmotility and uncertainty still exists as to whether this is a primary, and therefore pathogenetically relevant, or secondary phenomenon. It seems likely from the present and previous studies that it is a secondary phenomenon, possibly related to the degree of malnutrition.…”
Section: Resultsmentioning
confidence: 99%
“…As opposed to bulimics who vomit excessively or abuse laxatives, anorectics have less severe gastrointestinal problems. Gastrointestinal transit is known to be prolonged in patients with anorexia, affecting up to 80% of patients [38]. Alterations in antral motility and gastric atrophy are thought to be responsible for these problems.…”
Section: Medical Complicationsmentioning
confidence: 99%
“…The reason for this is poorly understood, although increased gastric emptying times are associated with profound weight loss and severe dietary restriction (interestingly, emptying times are decreased as renutrition programmes are completed), and autonomic dysfunction has also been implicated as a cause [20]. Gastric dilatation can occur and, if acute, may lead to gastric infarction or perforation [21].…”
Section: Gastrointestinalmentioning
confidence: 99%